Pemikiran Hadis Muhammad Al-Ghazali Dan Implikasinya Terhadap Tasyri` (Analisis Terhadap Kitab As-Sunnah An-Nabawiyyah Baina Ahl Al-Fiqh Wa Ahl Al-Ḥadīṡ) - Hafiz, Maulana; Anwar, Husnel; Is, Fadhilah (UIN Sumatera Utara Medan, 2023)
Muhammad al-Ghazali, a prominent hadith scholar from Egypt, is widely known as a leading figure in modern times. One of his significant contributions to the field of Hadith studies is a book entitled